2012
DOI: 10.1161/atvbaha.112.254664
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Smooth Muscle Emilin-1 Is a Regulator of Arteriolar Myogenic Response and Blood Pressure

Abstract: Objective-Emilin-1 is a protein of elastic extracellular matrix involved in blood pressure (BP) control by negatively affecting transforming growth factor (TGF)-β processing. Emilin1 null mice are hypertensive. This study investigates how Emilin-1 deals with vascular mechanisms regulating BP. Methods and Results-This study uses a phenotype rescue approach in which Emilin-1 is expressed in either endothelial cells or vascular smooth muscle cells of transgenic animals with the Emilin1 −/− background. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…Both vessels represent the prototype of resistance vessels involved in blood pressure homeostasis. 28,3841 As expected, enhanced vasorelaxation by AAV-LAV-BPIFB4 was associated with potentiation of eNOS phosphorylation (Online Figure XVB) and interestingly with a reduction of both systolic and diastolic blood pressure (Online Figure XVI). In contrast, transduction with AAV-WT-BPIFB4 did not exert molecular and vasorelaxant effects in this model (Online Figure XV).…”
Section: Resultssupporting
confidence: 64%
“…Both vessels represent the prototype of resistance vessels involved in blood pressure homeostasis. 28,3841 As expected, enhanced vasorelaxation by AAV-LAV-BPIFB4 was associated with potentiation of eNOS phosphorylation (Online Figure XVB) and interestingly with a reduction of both systolic and diastolic blood pressure (Online Figure XVI). In contrast, transduction with AAV-WT-BPIFB4 did not exert molecular and vasorelaxant effects in this model (Online Figure XV).…”
Section: Resultssupporting
confidence: 64%
“…PI3K/Akt signaling promoted voltage-dependent trafficking of Ca 2ϩ channels to the plasma membrane that increased Ca 2ϩ influx via L-type VOCC and thereby was involved in the myogenic response in mouse second-order mesenteric arteries (197,910). Genetic knockdown of Dicer for 5-6 wk to reduce the global role of microRNAs (miRNAs) lowered BP and myogenic tone in mesenteric arteries by reducing PI3K/Akt signaling and L-type VOCC activity (specifically the ␣2␦1 subunit) (101).…”
Section: Renal Autoregulatory Mechanismsmentioning
confidence: 99%
“…It has also been suggested that emilin-1, an elastin microfibril interface-located protein, is important to stabilize molecular interactions between VSMCs and elastic fibers, which maintain arterial morphology and prevent VSMC migration [81]. Emilin-1 also inhibits TGF-β activation, thus maintaining adequate arterial myogenic response and the integrity of arterial wall [82]. …”
Section: Mmp-2 Contributes To Vsmc Migration By Degrading Ecmmentioning
confidence: 99%